2017
DOI: 10.1902/jop.2016.160366
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Triglyceride Level and Gemfibrozil Consumption With Periodontal Status

Abstract: Patients with hypertriglyceridemia had worse periodontal status than healthy controls. Patients with hypertriglyceridemia who were taking gemfibrozil did not show significant differences in CAL and PD compared with untreated patients with hypertriglyceridemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We found no significant difference in periodontitis risk between the fibrate monotherapy and control groups. Similarly, Sayar et al 20 . reported no significant difference in periodontal parameters between fibrate users and nonusers in patients with hypertriglyceridemia.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…We found no significant difference in periodontitis risk between the fibrate monotherapy and control groups. Similarly, Sayar et al 20 . reported no significant difference in periodontal parameters between fibrate users and nonusers in patients with hypertriglyceridemia.…”
Section: Discussionmentioning
confidence: 93%
“…We found no significant difference in periodontitis risk between the fibrate monotherapy and control groups. Similarly, Sayar et al 20 reported no significant difference in periodontal parameters between fibrate users and nonusers in patients with hypertriglyceridemia. Although most studies show local delivery of antihyperlipidemic agents (mostly statins) improved the periodontal treatment outcome, 14 systemic statins or fibrate monotherapy did not influence the incidence of chronic periodontitis in patients with hyperlipidemia in our study.…”
Section: Eventsmentioning
confidence: 94%
See 2 more Smart Citations
“…However, no such association was found with periodontitis risk in male subjects ( 8 ). In the case of hyperlipidemia combined with periodontitis, the probing depth (PD) and clinical attachment loss (CAL) of patients were positively correlated with the levels of TG, TC, and LDL-C ( 9 , 10 ). Another cross-sectional study also showed that in patients with chronic periodontitis, the level of apolipoprotein B (apo B) in gingival crevicular fluid in the infected area was higher than that in the healthy area ( 11 ).…”
Section: Introductionmentioning
confidence: 99%